2015
DOI: 10.1177/0095399715593317
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Services and the Coproduction Puzzle: Filling in the Blanks

Abstract: This qualitative study analyzes an Italian hospital's endeavor to introduce a coproduction practice and the critical factors that affect its efficacy and efficiency. The empirical evidence shows that the meaningful engagement of the patient can be achieved only by factoring in the socioorganizational conditions of all stakeholders; that no divide exists between organizational production and client coproduction, rather, it is a relationship of interdependence that in turn raises critical issues; and that formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 50 publications
(65 reference statements)
0
34
0
Order By: Relevance
“…Different studies confirmed that the quality of the relationship between healthcare professionals and patients is a crucial factor for improving the adherence of patients [ 59 , 60 ]. Our results suggest the importance of supporting the introduction of new technological tools to innovate healthcare processes with a deep understanding of the psychosocial, relational, and pragmatic implication of such innovation: only “taking on board” the human resources implied in this organizational change, the challenge of innovating care process in an effective integrated model can be successful [ 61 , 62 ]. Healthcare professionals, in particular, need to be accompanied to understand and accept the value of such tools to improve their ability to follow and treat their type 2 diabetes patients.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies confirmed that the quality of the relationship between healthcare professionals and patients is a crucial factor for improving the adherence of patients [ 59 , 60 ]. Our results suggest the importance of supporting the introduction of new technological tools to innovate healthcare processes with a deep understanding of the psychosocial, relational, and pragmatic implication of such innovation: only “taking on board” the human resources implied in this organizational change, the challenge of innovating care process in an effective integrated model can be successful [ 61 , 62 ]. Healthcare professionals, in particular, need to be accompanied to understand and accept the value of such tools to improve their ability to follow and treat their type 2 diabetes patients.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests interesting further investigation on how the role of healthcare professionals and their attitudes to engagement are crucial assets with which to achieve activation. [ 70 – 75 , 68 , 67 ] Attitudes not given for granted since the concept of patient activation and engagement put into question the need of revisiting traditional power dynamics in the doctor-patients relationships [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…We believe that these results can also be useful in clinical practice, because a deeper understanding of patients’ experience of haemophilia can help the HCPs to consider the subjective, developmental, and cultural aspects that often remain unstated within interactions, thus fostering therapeutic alliance with them (Khair, 2013 ; Sorrentino, Guglielmetti, Gilardi, & Marsilio, 2015 ). In particular, this explorative study suggests the following considerations: counselling for PWH should address social and family relations including the fear of stigma, the fear of rejection, lack of confidence, and communication with carers who tend to overprotect PWH; HCPs should take into account that the fear of HIV/HCV infection through blood can still be present, even in rich developed countries; the interpersonal relationships with HCPs, economic concerns, and the perceived costs of the illness should also be addressed, particularly in the context of private health care systems, as in the USA; psychosocial interventions and HCPs should take into account the issue of pain management to help PWH to manage frustration and avoid becoming psychologically dependent on painkillers (Elander & Barry, 2003 ; Montali, et al, 2011 ); and finally, it is important to analyse the explanations that people give themselves about being ill, identifying models that refer to faith, fate, and/or genetics.…”
Section: Discussionmentioning
confidence: 99%